PEMODELAN ALJABAR LINIER UNTUK MENILAI KINERJA HIMPUNAN MAHASISWA TEKNOLOGI INFORMASI PERIODE 2025/2026: Linear Algebra Modeling for Assessing the Performance of the Information Technology Student Association for the 2025/2026 Period - Masdiansa, Anca; Permana, Handika Dwi (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2026)
This study aims to evaluate the performance of the Information Technology Student Association (HMTI) using a linear algebra modeling approach as a quantitative assessment method. Five main aspects were examined, including leadership, communication and coordination, program implementation, member involvement, and overall organizational effectiveness. The data were collected using a Likert-scale questionnaire administered to HMTI members and processed through vector representation and dot product operations to obtain a final performance score. The results indicate that HMTI’s performance is categorized as fair–good, with leadership and member involvement contributing the most to the overall score. Meanwhile, communication and coordination remain the lowest-rated aspect, significantly affecting the final evaluation results. These findings show that linear algebra modeling can provide an objective and measurable assessment, making it a reliable evaluation tool to support the continuous improvement of student organization governance.